Effects of Agricultural Practices on Water Quality in River Basins in United States - Harris, Daniel (International Journal of Environmental Sciences, 2021)
Purpose: To aim of the study was to analyze the effects of agricultural practices on water quality in river basins in United States. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Agricultural practices in the U.S., particularly fertilizer and pesticide use, significantly degrade water quality in river basins. Excessive nutrient runoff causes eutrophication, harmful algal blooms, and oxygen depletion, while pesticide use contaminates both surface and groundwater. Soil erosion and irrigation return flows further contribute to water quality issues by increasing sediment and nutrient pollution. Unique Contribution to Theory, Practice and Policy: The theory of ecological modernization, the tragedy of the commons & the systems theory may be used to anchor future studies on the effects of agricultural practices on water quality in river basins in United States. Farmers should be encouraged to adopt best management practices (BMPs), such as reduced pesticide use, organic farming, and crop rotation, which have been shown to reduce agricultural runoff and improve water quality. Policies should be enacted or strengthened to regulate the use of fertilizers and pesticides, particularly in regions where intensive agriculture is prevalent.